СРОЧНО 4(4-3x)(2-x)(1+2x)-3(3-4x)(2+x)(1-2x)=-43(2x+5)(x+2)-18

СРОЧНО 4(4-3x)(2-x)(1+2x)-3(3-4x)(2+x)(1-2x)=-43(2x+5)(x+2)-18
Гость
Ответ(ы) на вопрос:
Гость
32 - 68x^2 + 24x + 24x^3 - (3*(3 - 4x))(2 + x)(1 - 2x) = -43(2x+5)(x+2)-18 32 - 68x^2 + 24x + 24x^3 - 18 - 24x^3 - 18x^2 + 51x = -43(2x+5)(x+2)-18 32 - 68x^2 + 24x + 24x^3 - 18 - 24x^3 - 18x^2 + 51x = - 430 - 387х - 86х^2 - 18 Сокращаем, получаем: 462 + 462*x = 0 462x=−462 x = -462 / (462) Получим ответ: x = -1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы